2017
DOI: 10.1007/s11892-017-0885-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Racial/Ethnic Disparities in Type 2 Diabetes in Youth

Abstract: Purpose of Review Pervasive disparities in T2DM among minority adults are well-documented, and scholars have recently focused on the role of social determinants of health (SDOH) in disparities. Yet, no research has summarized what is known about racial/ethnic disparities in youth-onset T2DM. This review summarizes the current literature on racial/ethnic disparities in youth-onset T2DM, discusses SDOH that are common among youth with T2DM, and introduces a conceptual model on the possible role of SDOH in youth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 26 publications
3
65
1
1
Order By: Relevance
“…As in our study, others showed substantial proportions (≥40%) of subjects come from the most deprived families . The conceptual model for SDOH in youth with T2D proposes social determinants such as low family income, low parental education and higher levels of stress (in parents/caregivers and youth) are more prevalent in some ethnic minorities leading to both onset of T2D and poorer glycemic control acting via mediators like poorer lifestyle choices, healthcare access, family knowledge and coping skills and management of chronic diseases . Attitudes of healthcare providers when treating CYP from diverse ethnic and socioeconomic backgrounds could be another explanatory factor though not as significant as those above and harder to assess in observational studies like ours.…”
Section: Discussionsupporting
confidence: 53%
“…As in our study, others showed substantial proportions (≥40%) of subjects come from the most deprived families . The conceptual model for SDOH in youth with T2D proposes social determinants such as low family income, low parental education and higher levels of stress (in parents/caregivers and youth) are more prevalent in some ethnic minorities leading to both onset of T2D and poorer glycemic control acting via mediators like poorer lifestyle choices, healthcare access, family knowledge and coping skills and management of chronic diseases . Attitudes of healthcare providers when treating CYP from diverse ethnic and socioeconomic backgrounds could be another explanatory factor though not as significant as those above and harder to assess in observational studies like ours.…”
Section: Discussionsupporting
confidence: 53%
“…Research clearly demonstrates the relationship between SES and diabetes. Studies have found that low family income, parental education, and high youth stress are common among families of minority youth with T2DM, noting their influence on disparities in diabetes onset, quality of life, and family burden (26,71). Walker and colleagues (138) focus on income and stress as key determinants of poor glycemic control.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…As ethnicity overlaps with SES indicators (e.g., parental educational attainment) [30,31] and as parental educational attainment has a strong protective influence on academic achievement of youth, researchers have been interested in decomposing the contribution of ethnicity from SES (e.g., parental educational attainment) in explaining ethnic differences in academic achievement [32][33][34]. The results of this line of research are, however, conflicting.…”
Section: Introductionmentioning
confidence: 99%